Past, present, future of agricultural tractors - O. N. Didmanidze; S. N. Devyanin; Ye. P. Parlyuk (Аграрная наука Евро-Северо-Востока, 2020)
The development of tractor design is closely related to its technological updating, improving environmental performance and increasing usability. Study of this problem in a historical context shows the unity in approaches of various agricultural tractor manufacturers to tractor design aimed at increased productivity and reduced operation costs in accordance with the requirements for agronomic and environmental performance. The main task of the first-generation tractors was to develop traction for agricultural work with maximum productivity and cost-effectiveness. Solution of these problems required further development of the tractor theory and the idea of the processes quality, and ensured the optimization of design and performance. As a result, the designs of tractors from different manufacturers developed in the same direction. Modern tractors are equipped with electronically controlled turbocharged diesel engines and have systems reducing toxicity of the exhaust gases. Power transmission of the tractors is implemented either with a robotic gearbox without interrupting the power flow, or in a continuously variable format, which ensures a more optimized operating mode. While for small-traction-class tractors stepless power transmission is provided with a mechanical variable speed gear, the rest of the tractors require electronicallycontrolled hydromechanical transmissions. As the capacity of power stations grows and an extensive power grid based on renewable energy resources is developed, the demand for electric tractors is to be increased. Tractors with hybrid power plants are likely to be produced at the transitional stage of development. They have the advantages of controlling processes in the machine and tools, the ability to provide agricultural implements with electric power for carrying out their work processes and ensuring their active drive to develop traction as well.